Exploring the Role of Government Fiscal Stimulus on Financial Markets During Global Recessions - Eni Minarni (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Global economic recessions have historically triggered severe disruptions in financial markets, leading to declining investment, reduced liquidity, and loss of investor confidence. In response, governments often employ fiscal stimulus policies as a countercyclical measure to restore stability and promote economic recovery. This research aims to examine the effects of government fiscal stimulus on financial markets during global recessions, focusing specifically on the 2008 financial crisis and the 2020 COVID-19 pandemic recession. Using a qualitative research method with a literature review approach, this research synthesizes previous research findings to analyze how fiscal interventions influence stock market performance, bond yields, exchange rates, and overall economic recovery. The findings reveal that fiscal stimulus generally leads to positive stock market performance, lower bond yields, and mixed reactions in exchange rates. The research also highlights long-term fiscal sustainability concerns, including rising public debt and potential inflationary pressures. The results conclude that well-designed and timely fiscal policies are essential to restoring market confidence and stabilizing economies during periods of global crisis. This research contributes to the existing literature by providing a comparative analysis of fiscal stimulus effects across two major global recessions and offering valuable insights into the broader implications for financial market dynamics.